Diffusion and Intravoxel Incoherent Motion MR Imaging–based Virtual Elastography: A Hypothesis-generating Study in the Liver - Le Bihan, Denis; Ichikawa, Shintaro; Motosugi, Utaroh (Radiology, 2017)
Purpose To investigate the potential of diffusion magnetic resonance (MR) imaging to provide quantitative estimates of tissue stiffness without using mechanical vibrations in patients with chronic liver diseases and to generate a new elasticity-driven intravoxel incoherent motion (IVIM) contrast. Materials and Methods This retrospective study, conducted from January to April 2016, was approved by an institutional review board that waived the requirement for informed consent. Fifteen subjects were included (13 men and two women; mean age ± standard deviation, 73 years ± 8). MR elastography and diffusion MR imaging were performed at 3 T. A search for an empirical relationship between MR elastographic shear modulus, µ , and a shifted apparent diffusion coefficient (sADC) was performed. The sADC was then inverted to estimate patient liver shear modulus directly from diffusion MR imaging signals. Results A significant correlation (r = 0.90, P = 1 · 10 ) was observed between µ and sADC calculated by using diffusion MR imaging signals acquired with b values of 200 (S ) and 1500 (S ) sec/mm (sACD ). On the basis of the relationship between the µ and sADC , a diffusion-based shear modulus, µ , could be estimated with the following equation: µ = (-9.8 ± 0.8) ln(S /S ) + (14.0 ± 0.9). IVIM virtual elastograms also could be generated to reveal new contrast features in lesions, depending on pseudovibration frequency and amplitude. Conclusion Diffusion MR imaging, through a calibration of sADC with standard MR elastography, can be converted quantitatively into shear modulus without using mechanical vibrations to provide information on the degree of liver fibrosis; these virtual elastograms require only two b values to be acquired and processed. Propagating shear wave can also be emulated, leading to a new elasticity-driven IVIM contrast with ranges of virtual vibration frequencies and amplitudes not limited by MR elastography or MR imaging hardware capacities. RSNA, 2017 Online supplemental material is available for this article.